Slavoj Žižek - Wall, Tony. author. aut Link
IX, 64 p. 2 illus.
Keywords: Žižek demands we take a long, hard look at the painful reality of education in contemporary capitalist society, and to actively seek out its ‘trouble in paradise’: Why is it education is supposedly failing to meet the demands of our society? Why is it there are record levels of stress for teachers? Why is it there is a record level of complaints from our university students? How is it now possible to compare a higher education course with a vacuum cleaner, toaster or television? This book illuminates aspects of Žižek’s ideas which sheds light into these modern challenges and tensions in education, and considers alternative ways forward. Though Žižek frustrates as much as he inspires with his own recipe of Lacan, Hegel and Marx, this book aims to give an entry route into Žižekian critique of education, a topic area he very rarely directly talks about.